2013
DOI: 10.1007/s00382-013-1726-8
|View full text |Cite
|
Sign up to set email alerts
|

Natural variability of summer rainfall over China in HadCM3

Abstract: Summer rainfall over China has shown decadal variability in the past half century, which has resulted in major north-south shifts in rainfall with important implications for flooding and water resource management. This study has demonstrated how multi-century climate model simulations can be used to explore interdecadal natural variability in the climate system in order to address important questions around recent changes in Chinese summer rainfall, and whether or not anthropogenic climate change is playing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…However, the decreasing trends of EASM under external forcing is weaker than the observation, as evidenced in the circulation trend pattern (Figure b), SAT trend magnitude (Figure b). This discrepancy indicates that the internal variability mode of PDO may play a dominant role in the monsoon weakening as previously suggested [ Li et al ., ; Lei et al ., ; Zhou et al ., ], while the aerosol forcing plays a secondary or complementary role. Considering the model uncertainty and nonlinearity, how to determine the relative contributions of internal variability and external forcing deserves further study.…”
Section: Summary and Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, the decreasing trends of EASM under external forcing is weaker than the observation, as evidenced in the circulation trend pattern (Figure b), SAT trend magnitude (Figure b). This discrepancy indicates that the internal variability mode of PDO may play a dominant role in the monsoon weakening as previously suggested [ Li et al ., ; Lei et al ., ; Zhou et al ., ], while the aerosol forcing plays a secondary or complementary role. Considering the model uncertainty and nonlinearity, how to determine the relative contributions of internal variability and external forcing deserves further study.…”
Section: Summary and Discussionmentioning
confidence: 73%
“…Recently, Lei et al . [] suggested that both internal variability and anthropogenic forcing play roles in the observed weakening of EASM. Up to now, there is no consensus on the mechanisms of EASM weakening [ Zhou et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…P . Li et al ., 2010; Zhou et al ., ; Lei et al ., ], while ADRF plays a secondary or complimentary role.…”
Section: Model Simulations and Theories Of Aerosol And Monsoon Interamentioning
confidence: 99%
“…The EASM exerts a dominant effect on the summer climate in East Asia, providing about 40–50% of the annual mean precipitation over southern China and about 60–70% over northern China [ Lei et al ., , ; Song et al ., ]. Some studies found a weakening trend and southward migration of the precipitation zone of EASM beginning in the late 1970s [ Wang , ; Yu et al ., ; Xu et al ., ; Ding et al ., , ; Zhou et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…The possible mechanisms for the interdecadal change in the EASM is an active research topic [ Zhou et al ., ; Song et al ., ]. Various factors, such as sea surface temperature (SST) variability [ Xue , ; Wang , ; Yang and Lau , ; Li et al ., ; Zhou and Zou , ], sensible heat flux over the Tibetan Plateau [ Ding et al ., ; Wu et al ., ; Liu et al ., ], anthropogenic forcing (aerosols and greenhouse gases) [ Xu , ; Menon et al ., ; Ueda et al ., ; Liu et al ., ; Li et al ., ; He et al ., ; Wang et al ., ; Song et al ., ; Zhu et al ., ], and natural decadal variability [ Jiang and Wang , ; Lei et al ., , ] have been linked to the interdecadal change in the EASM. Song et al .…”
Section: Introductionmentioning
confidence: 99%